Axicon-based Bessel beams for flat-field illumination in total internal reflection fluorescence microscopy - Schreiber, Benjamin; Elsayad, Kareem; Heinze, Katrin G. (Optics Letters, 2017)
Total internal reflection fluorescence microscopy (TIRF-M) provides low-invasive high-contrast surface imaging with optical sectioning of typically 100–200 nm. Thus, TIRF-M has become an established tool for imaging surfaces, including cell membranes. For TIRF-M, a homogenous evanescent field of excitation over the whole field of view is generally desired for quantitative microscopy; however, this is not necessarily straightforward to generate with Gaussian beams. In recent years, several improvements on TIRF-M have been developed that have addressed non-uniform scattering fringes and other artifacts. Here, we introduce a cost-effective TIRF setup with a very low degree of complexity and no moving parts, which provides a flattop-like excitation profile. The setup uses a tunable laser ring zoom focus system to generate a full 360° TIRF illumination. Two axicon lenses and one focus lens allow for generation and control of the ring diameter to tune the TIRF excitation angle. We show that 360° laser illumination in combination with a radial polarizer will generate an evanescent Bessel-beam excitation field that exhibits a flattop intensity over an extended part of the field of view, and demonstrate the advantages of this axicon-based Bessel beam illumination for live-cell imaging.
CRIS-Team Scopus Importer:2023-03-23